Psychosocial Skills as a Protective Factor and Other Teacher Recommendations for Online Harms Prevention in Schools: A Qualitative Analysis - Throuvala, Melina A.; Griffiths, Mark D.; Rennoldson, Mike; Kuss, Daria J. (Frontiers in Education, 2021)
Rising prevalence of mental disorders among children and adolescents in the United Kingdom has arguably been associated with increased levels of problematic smartphone use and social media use, rendering the need for health promotion at a school level. However, evidence on how teachers may best support media literacy and emotional wellbeing is lacking. The present study explored perceptions of adolescent online engagement and recommendations of how schools could prevent the experience of online harms during adolescence through qualitative interviews with teachers (N = 9, Mage = 39.2 years, SD = 7.74). Results were analysed using thematic analysis and provided the following themes in terms of recommendations for online harms: i) schools in transition and redefining expectations, ii) a modular approach to media and emotional literacy, iii) media and emotional literacy teacher training, and iv) encourage dialogue and foster psychosocial skills. Psychosocial skills were further analysed as critical components of perceived online harm prevention into the following categories: i) self-control and emotion regulation skills, ii) digital resilience and assertiveness skills, iii) social and emotional intelligence and metacognitive skills to encourage balanced use and emotional health. Findings corroborated the need for an increasing health promotion role of teachers and school counsellors and in the contribution of students’ cognitive and emotional development through skill acquisition. Implications are discussed for the role of educational settings in prevention of online harms, while preserving the significant benefits of digital media for education and social connection, and for the prompt identification and referral of problematic users to adolescent mental health services.